Chemical composition of bunya nuts (Araucaria bidwillii) compared to Araucaria angustifolia and Araucaria araucana species. (January 2023) - Moura Nadolny, Jaqueline; Best, Odette; Netzel, Gabriele; Shewan, Heather M.; Dao Thi Phan, Anh; Smyth, Heather E.; Stokes, Jason R.
Graphical abstract: Highlights: Bunya nuts chemical composition was studied for the first time. The bunya nut kernel contains mainly moisture and starch. The husks and inner coating of the bunya nuts are rich in phenolic compounds. The bunya nut chemical composition is similar to pinhão (Brazil) and piñones (Chile). Similarities among these three species allow interchange of knowledge and applications. Abstract: Three of nineteen Araucaria tree species from around the world produce large edible seeds. While composition is established for edible pinhão and piñones nuts from Brazil and Chile, respectively, the first detailed characterisation for the composition of edible Araucaria bidwillii (bunya nut) from Australia is provided. Almost half of the kernel weight is moisture and the main component in the dried kernel is starch. Whilst low in protein and fat, it contains all essential amino acids and half the fatty acids are polyunsaturated (Omega-3 and 6). Bunya nuts are a source of dietary fibre, folate and minerals (Cu, Mn, Fe, Mg), while the nut husks and inner coating are high in phenolics, mainly catechin. The composition supports the Traditional Knowledge of Aboriginal Australians that the bunya nut is an energy dense and nutrient rich food. Similarities in the composition among the three different edible varieties were found, which should assist in developing sustainable value chain propositions via shared knowledge on processing and utilisation.